ACE2 enzymatic role in the SARS-CoV-2 activation: a perspective through the evolutionary promiscuity and substrate diversity of enzymes (Journal of Ideas in Health, 2021)
The SARS-CoV-2 is an RNA B type β-coronavirus that distinguishes itself from previous coronaviruses by its high infectivity and mortality rates. The mechanism of viral entry into the host cell via ACE2 is currently under research. Several proteases have been nominated to activate the virus but identifying the exact enzyme/enzymes is missing.   Moreover, recent work suggests that TMPRSS2 cannot be the enzyme to cleave the SARS-CoV-2 spike or that multiple proteases contribute to SARS-CoV-2 activation. The multitude of proteases that have been nominated to activate the virus suggests that the consensual identification of the precise, key enzyme is still missing. In this context, we synthesize the current controversies regarding the putative enzymes involved in SARS-CoV-2 infectivity and analyze whether ACE2 could have unexpected enzymatic roles in this process, besides its acknowledged receptor role. We hypothesize that ACE2 plays an enzymatic role as well in SARS-CoV-2 activation. Understanding the exact roles of ACE2 in COVID-19 is capital for the future design of specific, efficient therapies and deserves dedicated research. Our conviction is therefore not "if", “but” "when" will the researchers start to wonder about what is hidden behind the apparent only role of ACE2 as a receptor for SARS-CoV-2.
Keywords: ACE2, SARS-CoV-2, COVID-19, enzymatic activity, enzymatic promiscuity, TMPRSS2, ADAM-17, Romania